Hubungan Pola Makan Dengan Tekanan Darah Pada Klien Hipertensi - natalya, wiwiek; madjid, sekar zahra (LPPM UNIKAL, 2024)
The prevalence of hypertension in Central Java is the largest non- communicable disease, while according to the Pemalang District Health Office, the highest hypertension occurs in Taman District, especially the Banjardawa Health Center (93.05%). High blood pressure is closely related to people's diet. Uncontrolled eating patterns such as high sodium, high fat and lack of potassium trigger high blood pressure. The study aimed to determine the correlations between diet and high blood pressure at the Banjardawa Health Center. The design of this study is correlation analytics, a cross-sectional approach, with accidental sampling techniques with a sample of 78 respondents, instruments using dietary questionnaires and sphygmomanometer tools to determine the correlation between diet and blood pressure using the Pearson product-moment test. Respondents' diet mean (21.49). On systolic blood pressure, the respondents mean (159.40). At diastolic blood pressure, the respondents mean (92.83). The results of the hypothesis test using the Pearson product-moment test results of eating patterns with systolic blood pressure value 0.01 (<0.05) with a correlation value of r (0.290), the results of eating patterns with diastolic blood pressure value 0.01 (<0.05) with a correlation value of r ( 0.348). Accepted with a low correlation strength parameter, namely, there is a relationship between diet and blood pressure in hypertensive people at the Banjardawa Health Center, Pemalang Regency. Conclusion:A Correlation exists between diet and blood pressure in hypertensive people at the Banjardawa Health Center, Pemalang Regency.